2021
DOI: 10.1007/s11606-021-07063-2
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Health System Factors and Utilization of Routine Laboratory Tests in Clinical Teaching Units: a Cohort Analysis

Abstract: BACKGROUND: Few studies have looked at health system factors associated with laboratory test use. OBJECTIVE: To determine the association between health system factors and routine laboratory test use in medical inpatients. DESIGN: We conducted a retrospective cohort study on adult patients admitted to clinical teaching units over a 3year period (January 2015 to December 2017) at three tertiary care hospitals in Calgary, Alberta. PARTICIPANTS: Patients were assigned to a Case Mix Group+ (CMG+) category based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…We excluded 74 540 in-hospital patient-days that did not belong in the top 10 CMG+ categories. Our final cohort included 36 667 hospital patient-days with 4324 unique patients over 5071 hospital admissions 11 (Figure 1). The top 10 CMG+ groups were as follows: heart failure without coronary angiogram, other or unspecified sepsis or shock, chronic obstructive pulmonary disease, cirrhosis or alcoholic hepatitis, viral or unspecified pneumonia, diabetes, renal failure, gastrointestinal hemorrhage, respiratory failure and disorders of fluid or electrolyte imbalance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We excluded 74 540 in-hospital patient-days that did not belong in the top 10 CMG+ categories. Our final cohort included 36 667 hospital patient-days with 4324 unique patients over 5071 hospital admissions 11 (Figure 1). The top 10 CMG+ groups were as follows: heart failure without coronary angiogram, other or unspecified sepsis or shock, chronic obstructive pulmonary disease, cirrhosis or alcoholic hepatitis, viral or unspecified pneumonia, diabetes, renal failure, gastrointestinal hemorrhage, respiratory failure and disorders of fluid or electrolyte imbalance.…”
Section: Resultsmentioning
confidence: 99%
“…20 Related research has shown other impacts of breaks in physician continuity such as increases in redundant use of diagnostic testing. 11,21,22 More research is needed to identify the full spectrum of downstream outcomes of breaks in attending physician continuity of care on CTUs at the patient, provider and health-systems levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, on the CTUs, the changes did not sustain after the study period. Recognising the additional merits of system-focused interventions on effectiveness and sustainability,29 our team has worked with operational and medical team leaders in advance of the launch of a new provincial harmonised EMR system to design system-level changes including modifications of order sets and entry processes 30. We are currently examining the effect of the provincial harmonised EMR deployment on the use of laboratory tests.…”
Section: Discussionmentioning
confidence: 99%